The double-roof paradox in buildings of the ecuadorian Amazon: thermal comfort strategies and the implications of these constructions for the urban landscape (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
In Amazonian cities of Ecuador, an empirical climate adaptation practice has become widespread: the self-managed construction of double roofs over concrete buildings. This strategy emerged as a mitigation response to control the effects of the warm-humid climate, characterized by high temperatures, intense solar radiation, and constant rainfall. Its proliferation has revealed deficiencies in conventional construction practices and a lack of integration of bioclimatic criteria in the initial design stages. From an urban perspective, the repeated implementation of this practice generates distinctive interpretations of the cityscape, creating unforeseen typologies that contribute to an unplanned urban identity. From a regulatory standpoint, this phenomenon reflects legal and planning gaps that allow the consolidation of informal extensions. This practice reveals a tension between individual solutions adopted by inhabitants and their collective impacts on the urban landscape. The study concludes that it is urgent and necessary to rethink Amazonian construction models by integrating bioclimatic strategies from the earliest design phases.